2016
DOI: 10.1111/1750-3841.13579
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Growth of Probiotic Lactic Acid Bacteria in Refrigerated Pickle Products

Abstract: We examined 10 lactic acid bacteria that have been previously characterized for commercial use as probiotic cultures, mostly for dairy products, including 1 Pediococcus and 9 Lactobacilli. Our objectives were to develop a rapid procedure for determining the long-term survivability of these cultures in acidified vegetable products and to identify suitable cultures for probiotic brined vegetable products. We therefore developed assays to measure acid resistance of these cultures to lactic and acetic acids, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…The loss of viability of the LGG increased over time for the CRG beverage ( P < 0.05). Similar behavior was reported by Fan, Breidt, Price, and Pérez‐Díaz (2017) for L. acidophilus in cucumber juice stored at 4 °C (Fan et al., 2017). Previous research demonstrated that Lactobacillus rhamnosus Lr‐32 survival in a whey‐based beverage formulated with Psidium guajava pulp did not show significant differences from the values determined at 7 and 14 days (Buriti, Freitas, Egito, & dos Santos, 2014).…”
Section: Resultssupporting
confidence: 86%
“…The loss of viability of the LGG increased over time for the CRG beverage ( P < 0.05). Similar behavior was reported by Fan, Breidt, Price, and Pérez‐Díaz (2017) for L. acidophilus in cucumber juice stored at 4 °C (Fan et al., 2017). Previous research demonstrated that Lactobacillus rhamnosus Lr‐32 survival in a whey‐based beverage formulated with Psidium guajava pulp did not show significant differences from the values determined at 7 and 14 days (Buriti, Freitas, Egito, & dos Santos, 2014).…”
Section: Resultssupporting
confidence: 86%
“…4). This is expected since Lactobacillaceae and Leuconostocaceae are the primary bacterial actors early in vegetable fermentations and other food microbiomes (2,(15)(16)(17)(18)(19). Similarly, high abundances of Leuconostocaceae were observed in the fermentation room, both on the floor and in filled barrels, and on most door handle surfaces ( Fig.…”
Section: Resultsmentioning
confidence: 78%
“…For instance, some species in the genus Weissella have potential as probiotics, owing to their ability to produce exopolysaccharides (e.g., Weissella cibaria and Weissella confusa ) ( Fusco et al, 2015 ). Moreover, a number of studies have reported the dominant effective microbes present in traditionally fermented pickles, fermented dough, yogurt, and fermented wine, as well as the production of foods fermented with LAB strains from their natural microbiota ( Ben Omar and Ampe, 2000 ; Pinto et al, 2015 ; Fan et al, 2017 ; Motato et al, 2017 ). These analyses, highlighting the diversity and richness of microbial communities among the fermented FVJs, provided the foundation for the separation of LAB isolates ( Pinto et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%